จากอนุภาคมูลฐาน ถึง หลุมดำ (I) - หลวงทิพย์, วาสุเทพ; มุศิริ, สุพจน์; พุ่มสะอาด, เข้ม; ศุภนาม, นพมณี; อุทยารัตน์, ปฏิภาณ (Science Essence Journal, 2017)
บทคัดย่อ บทความวิชาการนี้แบ่งเป็นสองส่วน โดยมีจุดมุ่งหมายในการแสดงให้เห็นถึงบทบาทของฟิสิกส์พลังงานสูงที่มีต่อความเข้าใจฟิสิกส์สมัยใหม่ รวมถึงความท้าทายที่นักฟิสิกส์เผชิญอยู่ในปัจจุบัน บทความวิชาการส่วนที่ 1 นี้จะกล่าวถึงฟิสิกส์ของอนุภาค โดยเริ่มจากการจำแนกอนุภาคมูลฐานและแรงพื้นฐานในธรรมชาติ การเกิดมวลของอนุภาคมูลฐานผ่านกระบวนการฮิกซ์และอนุภาคฮิกซ์โบซอน นอกจากนี้ยังกล่าวถึงความเชื่อมโยงไปยังฟิสิกส์ใหม่ที่ยังไม่ถูกค้นพบ รวมทั้งการรวมตัวของอนุภาคมูลฐานควาร์ก เป็นอนุภาคที่เราคุ้นเคยแฮดรอน ผ่านแบบจำลองควาร์กและการศึกษาฟิสิกส์ของอนุภาคแฮดรอนโดยทฤษฎีการรบกวนเชิงไครัล - - - From Elementary Particles to Black Holes (I) ABSTRACT This article is the first part of the two-article-series review that aims to demonstrate the role of high-energy physics on the understanding of modern physics, as well as the challenges high-energy physicists are facing. The first part of the review concerns particle physics. The review starts from the classification of elementary particles and elementary forces. It then discusses the Higgs mechanism for the generation of particle masses, the appearance of the Higgs boson, and possible connections between Higgs physics and new, yet unknown, physics. Next, hadrons (particles that are familiar from everyday life) are covered in the context of the quark model. Finally, the review ends with the descriptions of hadronic physics in the framework of Chiral perturbation theory.